Caracterização da alteração hidrotermal e balanço de massa em rochas graníticas hospedeiras do Depósito Aurífero Tocantinzinho, Província do Tapajós - VIEIRA, Aline Silva (2019)
The Tocantinzinho auriferous deposit is located in the Tapajós Gold Province, in the southwestern part of the Pará state at about 200 km south of Itaituba town. The purpose of the present work was to perform a petrographic and chemical study of the hydrothermally altered granitic host rocks of that deposit, as well as to evaluate the absolute gains and losses of components resulting from the alteration and mineralization. The intrusive body is composed of monzogranites and syenogranites, whose main mineral constituents are microcline, plagioclase, quartz and biotite. These rocks show no significant penetrative planar structures. The hydrothermally altered granitoids reveal two varieties, informally named “salame” and “smoky”, which are distinguished from each other by their macroscopic aspect and colour. In a broad way, they are chemically very similar, although the latter is slightly richer in Fe2O3, MgO and volatiles. Both varieties show weak to moderate degree of alteration, being sericitization, chloritization, silicification, sulfidation, carbonatation and hematititzation the most important types. Mass balance calculations showed that, regardless the method used and for volume factors ranging from 0.8 to 1.2, the rocks gained mass in amounts that were dependent upon the alteration type. Fe2O3(t), MgO, Al2O3, CaO, K2O, H2O, C and S were the components most responsible for the mass gains, whereas SiO2 and Na2O accounted for the most significant mass losses, although the two former components have been gained during silicification and carbonation, respectively. For every m3 of altered granitic rock under isovolumetric conditions, estimates indicate gains varying from 24 to 114 kg of hydrothermal products, the highest values corresponding to sericitization of the smoky variety.